Solo works of mixed music with live electronics: A qualitative enquiry in timbre and gesture from the performer's perspective. (September 2016) - Boutard, Guillaume
The performance of mixed music with live electronics is challenging for performers. In this context, idiosyncratic sound processing and synthesis tools are developed specifically for each work, inclined to technological obsolescence, and thus creating transmission and preservation issues. Still, performers, especially in the case of solo works, develop an expertise over time and over multiple performances by multiple performers. From this perspective, the question of co-construction of meaning in relation to performance is especially relevant. We designed an experiment to study this process of co-construction of expertise and appropriation of live electronics from the perspective of instrumentalists. We commissioned four solo works (each one for a different instrument) and asked two instrumentalists (for each work) to play the piece during a concert. We used qualitative methods stemming from psychology of work to study the performance activity in relation to gesture and timbre from the point of view of instrumentalists. For each work, the instrumentalists were confronted with the traces of their own activity, that is to say, the video and audio recordings of their performance and, subsequently, with those of the other instrumentalist in his/her presence. The data was then compared to conceptual frameworks designed mainly in relation to instrumental music. This study provides us with a better understanding of the appropriation of live electronics by instrumentalists, the strategies for transmitting an expertise, and proposes theoretical and practical grounds for new frameworks for documenting and disseminating mixed music with live electronics.